2021
DOI: 10.1177/02841851211021035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of femoral head bone quality by Hounsfield units: a comparison with dual-energy X-ray absorptiometry

Abstract: Background Osteoporosis is associated with decreases in bone mineral density (BMD) and is diagnosed using dual-energy X-ray absorptiometry (DXA). Computed tomography (CT), performed in routine practice, can also be used to evaluate bone quality without additional cost. Purpose To determine whether Hounsfield units (HU), a standardized CT attenuation coefficient, measured from the femoral head correlated with DXA-measured BMD. Material and Methods We evaluated 82 patients (14 men, 68 women; mean age, 67 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Many studies have shown that the Hounsfield unit (HU) values of the bone trabecula obtained by a routine CT can be used to assess osteoporosis [5], such as in the lumbar spine [6][7][8], cervical spine [9,10], thoracic spine [11], femur [12], pelvis [13], and ulna [14]. In clinical practice, chest CT [15], a widely used and highly accessible test, can be used for lung cancer screening and chronic obstructive pulmonary disease detection.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the Hounsfield unit (HU) values of the bone trabecula obtained by a routine CT can be used to assess osteoporosis [5], such as in the lumbar spine [6][7][8], cervical spine [9,10], thoracic spine [11], femur [12], pelvis [13], and ulna [14]. In clinical practice, chest CT [15], a widely used and highly accessible test, can be used for lung cancer screening and chronic obstructive pulmonary disease detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a variety of alternative tools have been introduced to evaluate peripheral BMD, including radiographic absorptiometry, ultrasound, and conventional and quantitative computed tomography, particularly, the conventional CT method is one of the most widely used for identifying unrecognized diseases and is easy to [ 5 ]. Many studies have evaluated BMD on general CT scans of the spine, hip, and wrist obtained for reasons other than BMD [ 6 9 ]. Similarly, three recent literatures compared DXA data with Hounsfield unit (HU) measurements in the proximal humerus, and a significant association between HU values on shoulder CT and BMD as measured by DXA scan was [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another known drawback of DXA is the elevation of areal BMD measurements that can be seen in patients due to vascular calcification and/ or proliferations of the vertebrae (4,5). The use of conventional multi-slice computed tomography (MSCT) devices for volumetric measurements of BMD in the detection of osteoporosis has recently shown promising results (6,7). The bone structure as well as the BMD values are heavily affected in osteoporosis (8) and disconnections in the trabecular bone network have been shown to increase the risk of fractures in the vertebrae (9).…”
Section: Introductionmentioning
confidence: 99%